When did Indians become straight? kinship, the history of sexuality, and native sovereignty - Rifkin, Mark, 1974- (New York ; Oxford : Oxford University Press, 2011)
'When Did Indians Become Straight?' explores the complex relationship between sexual mores and shifting forms of Native American self-representation.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: American literature -- White authors -- History and criticism; American literature -- Indian authors -- History and criticism; Indians in literature; Homosexuality in literature; Self-determination, National, in literature; Indians of North America -- Kinship; Indians of North America -- Ethnic identity; Indians of North America -- Government relations